3D Orbital Reconstruction in a Patient with Microphthalmos and a Large Orbital Cyst—A Case Report. (2nd April 2016) - Mourits, D. L.; Wolff, J.; Forouzanfar, T.; Ridwan-Pramana, A.; Moll, A. C.; de Graaf, P.; Remmers, J. S.; Kraal-Biezen, E.; Hartong, D. T.
Abstract: Background : Orbital cysts are rare developmental anomalies that can occur in microphthalmic and anophthalmic patients. Such cysts can promote orbital growth and subsequently markedly increase the size of the orbit, which is commonly underdeveloped in these patients. Cyst removal is therefore generally dissuaded (at least) in the first 5 years. Clinical case : A 6-year-old boy with a microphthalmos and a cyst developed protrusion of his prosthetic eye and a swelling of the lower eyelid. MRI showed a large cyst causing distortion of the right orbit. Due to the expansive orbital growth and subsequent misfitting of the prosthesis, cystectomy and orbital floor reconstruction was performed using 3D technology. Conclusion : 3D imaging and printing enables exact delineation of orbital cysts and the adjacent bony structures. Furthermore it offers the possibility to plan an individual surgical approach and to design and fabricate a custom fit orbital floor implant.